2009
DOI: 10.1371/journal.pgen.1000549
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of the Basal Lineage Fungus Rhizopus oryzae Reveals a Whole-Genome Duplication

Abstract: Rhizopus oryzae is the primary cause of mucormycosis, an emerging, life-threatening infection characterized by rapid angioinvasive growth with an overall mortality rate that exceeds 50%. As a representative of the paraphyletic basal group of the fungal kingdom called “zygomycetes,” R. oryzae is also used as a model to study fungal evolution. Here we report the genome sequence of R. oryzae strain 99–880, isolated from a fatal case of mucormycosis. The highly repetitive 45.3 Mb genome assembly contains abundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
322
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 360 publications
(347 citation statements)
references
References 49 publications
14
322
0
2
Order By: Relevance
“…Differential selection across ploidy levels has been observed in different abiotic environments (e.g., Dhar et al 2011) and increased ploidy has been suggested to provide a selective advantage in adaptation to new environmental conditions (Pawlowska and Taylor 2004;Ma et al 2009). However, despite the strong selection pressure that is expected in serpentine soils and a report of possible influences of serpentine on the evolution of polyploids in K. arvensis (Kolář et al 2012), we did not find significant differentiation in genome size between the C. geophilum populations included in this study, suggesting that genetic and demographic processes are more important in shaping the genome size variation of this species than environmental selection in the form of home soil chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Differential selection across ploidy levels has been observed in different abiotic environments (e.g., Dhar et al 2011) and increased ploidy has been suggested to provide a selective advantage in adaptation to new environmental conditions (Pawlowska and Taylor 2004;Ma et al 2009). However, despite the strong selection pressure that is expected in serpentine soils and a report of possible influences of serpentine on the evolution of polyploids in K. arvensis (Kolář et al 2012), we did not find significant differentiation in genome size between the C. geophilum populations included in this study, suggesting that genetic and demographic processes are more important in shaping the genome size variation of this species than environmental selection in the form of home soil chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…We have selected (a) 14 popular white rot fungal strains – Ceriporiopsis subvermispora B (Fernandez-Fueyo et al 2012), Heterobasidion annosum v2.0 (Olson et al 2012), Fomitiporia mediterranea v1.0 (Floudas et al 2012), Phanerochaete carnosa HHB-10118 (Suzuki et al 2012), Pycnoporus cinnabarinus BRFM 137 (Levasseur et al 2014), Phanerochaete chrysosporium R78 v2.2 (Martinez et al 2004; Ohm et al 2014), Dichomitus squalens LYAD-421 SS1 (Floudas et al 2012), Trametes versicolor v1.0 (Floudas et al 2012), Punctularia strigosozonata v1.0 (Floudas et al 2012), Phlebia brevispora HHB-7030 SS6 (Binder et al 2013), Botrytis cinerea v1.0 (Amselem et al 2011), Pleurotus ostreatus PC15 v2.0 (Riley et al 2014; Alfaro et al 2016; Castanera et al 2016), Stereum hirsutum FP-91666 SS1 v1.0 (Floudas et al 2012), Pleurotus eryngii ATCC90797 (Guillen et al 1992; Camarero et al 1999; Ruiz‐Dueñas et al 1999; Matheny et al 2006); (b) 15 popular brown rot fungal strains – Postia placenta MAD 698-R v1.0 (Martinez et al 2009), Fibroporia radiculosa TFFH 294 (Tang et al 2012), Wolfiporia cocos MD-104 SS10 v1.0 (Floudas et al 2012), Dacryopinax primogenitus DJM 731 SSP1 v1.0 (Floudas et al 2012), Daedalea quercina v1.0 (Nagy et al 2015), Laetiporus sulphureus var v1.0 (Nagy et al 2015), Postia placenta MAD-698-R-SB12 v1.0 (Martinez et al 2009), Neolentinus lepideus v1.0 (Nagy et al 2015), Serpula lacrymans S7.9 v2.0 (Eastwood et al 2011), Calocera cornea v1.0 (Eastwood et al 2011), Gloeophyllum trabeum v1.0 (Floudas et al 2012), Fistulina hepatica v1.0 (Floudas et al 2015), Fomitopsis pinicola FP-58527 SS1 (Floudas et al 2015), Hydnomerulius pinastri v2.0 (Kohler et al 2015) and Coniophora puteana v1.0 (Kohler et al 2015); (c) 13 popular soft rot fungal strains – Trichoderma reesei v 2.0 (Martinez et al 2008), Rhizopus oryzae 99-880 from Broad (Ma et al 2009), Aspergillus wentii v1.0 (De Vries et al 2017), Penicillium chrysogenum Wisconsin 54-1255 (Van Den Berg et al 2008), Daldinia eschscholzii EC12 v1.0, Hypoxylon sp. CI-4A v1.0 (Wu et al 2017), Aspergillus niger ATCC 1015 v4.0 (Andersen et al 2011), Hypoxylon sp.…”
Section: Methodsmentioning
confidence: 99%
“…These new E-value cutoff scores were uniformly applied to the apicomplexan peptide datasets to classify PKs into groups. Our HMM library has previously been applied in the kinome characterization of Trichomonas vaginalis [113], Brugia malayi [114], E. cuniculi [115], the fungi Rhizopus oryzae [116] and Fusarium ssp. [117], and the algae Ectocarpus siliculosus [118] and Chlamydomonas reinhardtii [119].…”
Section: Identification and Classification Of Apicomplexan Pksmentioning
confidence: 99%